ePortfolios: A 360-Degree Approach to Assessment in Teacher Education - Puleng Modise, Mpho-Entle; Vaughan, Norman (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie, 2024)
ePortfolios are increasingly being used for teaching, assessing, and supporting students’ learning in higher education. With COVID-19 having forced many higher education institutions to move their education services and teaching to online spaces, ePortfolios have become more relevant in the assessment process as they are web-based. This self-study examines how ePortfolios are being used to support assessment practices in a South African and a Canadian teacher education program. Data comprised critical dialogue, notes, reflections, and conversations with students enrolled in both teacher education programs. Findings suggest that students use ePortfolios to integrate self, peer, and teacher/ expert feedback, which results in a 360-degree approach to assessment.